LIBRAS IN LAW AND SCHOOL PRACTICE: what we have and what we need - Fernandes, Cristiane Lima Terra (Momento - Diálogos em Educação, 2022)
In Brazil, the Brazilian Sign Language – Libras has been recognized as the language of the Brazilian deaf community since 2002, a recognition that has allowed advances, especially in the area of education. Timidly, Libras has been publicized in social spaces and in the media. However, stilltrained professionals are lacking to work not only in the area of education of deaf students but in the most varied social environments where deaf people circulate and need accessible communication. This paper presents the legal context in which Libras is inserted and occurs in the school practice, explaining what we have and what is still missing to achieve. There are bilingual schools in the country though in lower numbers than it is actually needed. Moreover, among most bilingual schools, a Libras first language curriculum is not being practiced. Most of them follow the model of teaching Libras to hearing people as a second language, or focus on teaching cultural issues of the deaf people with little emphasis on teaching the linguistic and grammatical aspects of the language. Such actions are due to limited debates on the formal teaching of Libras as a first language as well as due to the scarce training of Libras teachers.